Anatomi Zakat Mal (antara Ibadah Mahdhah dan Mu’amalah Maliyyah) - Rusdan Rusdan (LP2M STIT Palapa Nusantara, 2021)
There is a general view that is developing among the jurists' that zakat is a mahdhah worship which contains the side of mu'amalh maliyah ijtima'iyyah. As a mahdhah worship, zakat is ta'abbudi. At this point, submission and obedience are put forward so that there is no room for innovation and creation. While in its position as mu'amalh maliyah ijtima'iyyah it is ta'aqquli, so it is possible to make innovations and creations, both regarding the object of zakat, miqdar zakat (nishab and percentage of zakat), or other things that surround the zakat. The data used in this research is secondary data which is collected and obtained from literature studies, documents and other scientific publications. While the data analysis method used is a qualitative descriptive method, which is intended to comprehensively explain and analyze the position of zakat as mahdhah worship which contains mu'amalah maliyyah ijtima'iyyah which cannot be separated from the socio-economic aspects. Although it is understood that zakat mal contains aspects of mu'amalah maliyah ijtima'yyah, in addition to aspects of mahdhah worship which are ritual nuances and are ta'aqquli in nature, in practice the nuances of worship are more dominant, both at the theoretical-normative and practical-policy level. This is evident from the lack of progressive ijtihad to develop zakat miqdar (nishab and zakat percentage), zakat objects, and state policies. So far, the object of zakat has almost no development other than what the jurists have discussed in fiqh books which usually only revolves around a few commodities / business fields, such as zakat on gold and silver, zakat on livestock (usually limited to camels, cows, and goat), zakat on agriculture and certain fruits, zakat on commerce, and zakat for mining goods and hidden assets.